Penerapan Strategi Inquiring Minds Want To Know Pada Mata Pelajaran Ips Siswa Kelas V MI NU Sukamaju - Tika Riyana; Ayu Lestari (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang OKU Timur Sumatera Selatan, 2022)
Abstract: This study aims to obtain data on the implementation of the Inquiring Minds Want To Know strategy in social studies subjects for fifth grade students of MI NU Sukamaju. This study uses a qualitative approach with data with observations, interviews, and documentation. In analyzing the data, the writer uses the Miles and Huberman version of data analysis, namely; data reduction, data presentation, and drawing conclusions or verification. The results showed that the application of the Inquiring Minds Want To Know strategy in social studies subjects for class V MI NU Sukamaju students in KBM there were several steps, namely asking questions about the material to be delivered, encouraging students to answer anything according to their expectations, collecting and accommodating all answers. given by the student, from the question look for the right answer that is supported by the data and give the correct answer to the student. There are two challenges faced in implementing the Inquiring Minds Want To Know strategy in social studies subjects for class V MI NU Sukamaju students, namely students and the time allocation used, learning activities that lead students to express their ideas or opinions about a material this will make students scramble express his opinion so that it will be a little difficult to control student learning activities. The solution to the challenges faced in implementing the Inquiring Minds Want To know strategy in social studies subjects for fifth grade students at MI NU Sukamaju, namely to control student activities, teachers must master and understand students so that they can be conditioned and the learning process can take place well, while for time, teachers must more effectively as possible in using learning time such as when the opening is too long which results in reduced time for delivering material.